Membangun Peran Nilai – Nilai Pancasila Untuk Menciptakan Generasi Muda Di Sekolah Dasar Yang Damai - Sekarwangi, Dinda Putri; Damayanti, Alvina; Anggraeni, Putri Ayu; Kristina, Canda; Sunaryati, Titin (Jurnal Ilmiah Wahana Pendidikan, 2023)
Civic education in realizing peaceful schools in the midst of a pluralist society creates a challenge and diversity in life that is expected of a nation to create mutual respect and have a harmonious life without social conflict in a pluralist society. This paper aims to shape character and build awareness of the younger generation, especially students in the nation and state at school. Researchers used a qualitative approach and descriptive method as an illustration to obtain research results. The results of the study show that the role of civic education has an important role in realizing peaceful schools. According to Suyanto in Zulnuraini civics education is high character education in the character class which involves three activities namely cognitive (cognitive), feeling (feeling), and action (action) in building and cultivating good character to carry out life in society.